Whole-Genome Sequences of Xanthomonas euvesicatoria Strains Clarify Taxonomy and Reveal a Stepwise Erosion of Type 3 Effectors - Barak, Jeri D.; Vancheva, Taca; Lefeuvre, Pierre; Jones, Jeffrey B.; Timilsina, Sujan; Minsavage, Gerald V.; Vallad, Gary E.; Koebnik, Ralf (Frontiers in Plant Science, 2016)
Multiple species of Xanthomonas cause bacterial spot of tomato (BST) and pepper. We sequenced five Xanthomonas euvesicatoria strains isolated from three continents (Africa, Asia, and South America) to provide a set of representative genomes with temporal and geographic diversity. LMG strains 667, 905, 909, and 933 were pathogenic on tomato and pepper, except LMG 918 which was pathogenic on pepper but elicited a hypersensitive reaction (HR) on tomato. Furthermore, LMG 667, 909, and 918 elicited a HR on Early Cal Wonder 30R containing Bs3. We examined pectolytic activity and starch hydrolysis, two tests which are useful in differentiating X. euvesicatoria from X. perforans, both causal agents of BST. LMG strains 905, 909, 918, and 933 were nonpectolytic while only LMG 918 was amylolytic. These results suggest that these strains are all atypical to both X. euvesicatoria and X. perforans. Sequence analysis of all the publicly available X. euvesicatoria and X. perforans strains comparing seven housekeeping genes identified seven haplotypes with few polymorphisms. Whole genome comparison by average nucleotide identity (ANI) resulted in values of >99% among the LMG strains 667, 905, 909, 918, and 933 and X. euvesicatoria strains and >99.6% among the LMG strains and a subset of X. perforans strains. These results suggest that X. euvesicatoria and X. perforans should be considered a single species. ANI values between strains of X. euvesicatoria, X. perforans, X. allii, X. alfalfa subsp. citrumelonis, X. dieffenbachiae, and a recently described pathogen of rose were >97.8% suggesting these pathogens should be a single species and recognized as X. euvesicatoria as well. Analysis of the newly sequenced X. euvesicatoria strains revealed interesting findings among the type 3 (T3) effectors, relatively ancient stepwise erosion of some T3 effectors, additional X. euvesicatoria-specific T3 effectors among the causal agents of BST, orthologs of avrBs3 and avrBs4, and T3 effectors shared among xanthomonads pathogenic on various hosts. The results from this study support the finding that T3 effector repertoire and host range are fundamental for the study of host – microbe interaction but of little relevance to bacterial speciation.